Interrelationship of Efl Teachers' Challenges: A Case Study at Senior High School In Palopo - Amelia, Raisa Amelia; Jusriati, Jusriati; Sari, Puspa (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study investigates the interrelationship of challenges faced by English teachers in implementing effective language instruction at a senior high school in Palopo, South Sulawesi, Indonesia. Despite the growing emphasis on student-centered learning under the Kurikulum Merdeka framework, English teachers in semi-urban regional contexts continue to encounter multifaceted obstacles that interact and mutually reinforce one another, a dynamic that remains underexplored in existing literature. This study employed a qualitative case study design involving three English teachers at SMAN 5 Palopo as research participants, selected through purposive sampling. Data were collected through structured interviews, classroom observations conducted across six sessions, and documentation review, then analyzed using Miles and Huberman's interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal four interconnected categories of challenges: pedagogical challenges in managing heterogeneous student proficiency levels, learner-related challenges including low motivation, passive engagement, and mobile phone distraction, institutional challenges stemming from severely limited teaching facilities and the absence of professional development opportunities, and technological challenges reflecting both infrastructural constraints and the dual role of digital devices as both learning tools and sources of disruption. Critically, these challenges do not operate in isolation. A traceable causal chain emerges in which institutional resource scarcity constrains technological access, which limits pedagogical variety, which reduces student engagement, which in turn intensifies classroom management demands and further strains teachers' capacity for differentiated instruction. Teachers demonstrated adaptive strategies aligned with principles of scaffolding and motivational reinforcement, however, the sustainability of these strategies is contingent upon systemic institutional support. This study concludes that addressing EFL teaching challenges in regional Indonesian contexts requires coordinated action at the pedagogical, institutional, and policy levels.